Adjunctive Brivaracetam Therapy in Epilepsy: A Prospective Clinical Study: Adjunctive Brivaracetam Therapy in Epilepsy - Bughio, Abdul Hafeez; Lakhiar, Muslim Ali; Hussain Seelro, Sajid; Nabi Siyal, Noor; Maheshwary, Neeta; Iqbal Asif, Muhammad; Athar, Muhammad (Pakistan Journal of Health Sciences, 2025)
Epilepsy is one of those primary illnesses that affect the brain, and the population is estimated to be around 50 million people. Objective: To evaluate the efficacy and safety of adjunctive Brivaracetam therapy in adult patients with epilepsy. Methods: This observational, non-interventional, single-center study assessed the use of adjunctive Brivaracetam (BRV) in patients aged ≥16 years over six months (October 2023–March 2024). Eligible participants had stable antiepileptic drug (AED) regimens for at least one month before BRV initiation. Demographic data, seizure type, frequency, and intensity were documented at baseline, 3 months, and 6 months. The primary endpoint was the change in seizure frequency. Secondary outcomes included ≥50% seizure reduction, seizure freedom, and adverse events. Data were analyzed using SPSS version 23.0. Results: A total of 168 patients (mean age: 25.1 ± 12.9 years) received adjunctive BRV therapy. Partial seizures and comorbid depression were the most common indications for BRV use. Mean seizure frequency decreased from 5.26 ± 0.29 at baseline to 2.41 ± 0.24 at 3 months. All patients achieved seizure freedom by 6 months. Reported adverse effects were generally mild: somnolence 12 (7%), headache 10 (6%), and dizziness 9 (5%). Conclusions: Adjunctive BRV therapy demonstrated significant efficacy in reducing seizure frequency and achieving seizure freedom, with a favourable safety profile. These findings support BRV as a promising treatment option for patients with epilepsy unresponsive to conventional AEDs.